Polygenic Score for Smoking Is Associated With Externalizing Psychopathology and Disinhibited Personality Traits but Not Internalizing Psychopathology in Adolescence. (November 2021) - Hicks, Brian M.; Clark, D. Angus; Deak, Joseph D.; Liu, Mengzhen; Durbin, C. Emily; Schaefer, Jonathan D.; Wilson, Sylia; Iacono, William G.; McGue, Matt; Vrieze, Scott I.
We examined whether a polygenic score (PGS) for smoking measured genetic risk for general behavioral disinhibition by estimating its associations with externalizing and internalizing psychopathology and related personality traits at multiple time points in adolescence (ages 11, 14, and 17 years; N = 3, 225). The smoking PGS had strong associations with the stable variance across time for all the externalizing measures (mean standardized β = 0.27), agreeableness (β = −0.22, 95% confidence interval [CI] = [−0.28, −0.16]), and conscientiousness (β = −0.19, 95% CI = [−0.24, −0.13]) but was not significantly associated with internalizing measures (mean β = 0.06) or extraversion (β = 0.01, 95% CI = [−0.05, 0.07]). After controlling for smoking at age 17 years, the associations with externalizing, low agreeableness, and low conscientiousness remained statistically significant. The smoking PGS measures genetic influences that contribute to a spectrum of phenotypes related to behavioral disinhibition, including externalizing psychopathology and normal-range personality traits related to behavioral control but not internalizing psychopathology.